2020
DOI: 10.1016/j.neuroimage.2020.116619
|View full text |Cite
|
Sign up to set email alerts
|

Exploring linearity of deep neural network trained QSM: QSMnet+

Abstract: Recently, deep neural network-powered quantitative susceptibility mapping (QSM), QSMnet, successfully performed ill-conditioned dipole inversion in QSM and generated highquality susceptibility maps. In this paper, the network, which was trained by healthy volunteer data, is evaluated for hemorrhagic lesions that have substantially higher susceptibility than healthy tissues in order to test "linearity" of QSMnet for susceptibility. The results show that QSMnet underestimates susceptibility in hemorrhagic lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 48 publications
0
51
0
1
Order By: Relevance
“…Previous works have proposed to solve QSM dipole inversion with deep neural networks, including QSMnet, 26 QSMnet + , 28 QSMGAN, 29 VaNDI, 31 autoQSM 32 and DeepQSM 34 . The first five frameworks require reconstructing QSM first using conventional methods as the training labels, which may deviate from the ground truth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have proposed to solve QSM dipole inversion with deep neural networks, including QSMnet, 26 QSMnet + , 28 QSMGAN, 29 VaNDI, 31 autoQSM 32 and DeepQSM 34 . The first five frameworks require reconstructing QSM first using conventional methods as the training labels, which may deviate from the ground truth.…”
Section: Discussionmentioning
confidence: 99%
“…One example is a recent study by Jung et al, reporting the effects of susceptibility range. 56 In the study, the network was trained using healthy volunteer data, limiting the training range to healthy tissue values (Figure 3a). When the network generated the susceptibility map of a hemorrhagic patient, it produced underestimated susceptibility values in hemorrhagic lesions, which have far higher susceptibility values than those of normal tissue ( Figure 3).…”
Section: Current Challenges Of Deep Learning Qsmmentioning
confidence: 99%
“…Similarly, Jung et al showed that data augmentation using susceptibility value scaled maps can cover a wider range of susceptibility values, successfully reconstructing QSM maps for pathology. 56 Different from other fields, which require additional data acquisition for data augmentation, QSM can be benefited from the dipole model in generating augmentation data.…”
Section: Generalization In Deep Learning Qsmmentioning
confidence: 99%
“…Another focus will be to explore the possibility to incorporate processing methods that are not developed in MATLAB. Emerging techniques using deep learning have already shown very promising results with further improvement in QSM artefact reduction (Bollmann et al, 2019;Chen et al, 2019;Jung et al, 2020;Polak et al, 2020;Wei et al, 2019;Yoon et al, 2018;Zhang et al, 2020). As the implementations of these methods are primarily in Python, while there are rich resources already available in MATLAB and supported in SEPIA to perform tasks such as phase unwrapping and background field removal, it would be valuable for SEPIA to connect the two.…”
Section: Discussionmentioning
confidence: 99%
“…As the implementations of these methods are primarily in Python, while there are rich resources already available in MATLAB and supported in SEPIA to perform tasks such as phase unwrapping and background field removal, it would be valuable for SEPIA to connect the two. Up to now, most deep learning methods do not yet have the flexibility to cope with arbitrary slice orientation and resolution (Jung et al, 2020;Yoon et al, 2018), this would therefore require data re-sampling to a pre-defined space which can be done with a plethora of software available for neuroimaging data, but we believe this is to be outside the scope of this toolbox. We also consider the compatibility between the SEPIA input and outputs data with BIDS (Gorgolewski et al, 2016), moving toward the standardisation of input and output phase data format and structure.…”
Section: Discussionmentioning
confidence: 99%